ANALISIS PENGGUNAAN TRANSPORTASI SUNGAI DI WILAYAH MAHAKAM ULU - Sianturi, Lidwina Sri Ayu DR; Long, Flora Emiliana; Sandjaja, Gregorius; Angkat, Hokbya R.S (JMTS: Jurnal Mitra Teknik Sipil, 2025)
Mahakam Ulu Regency is characterized by a topography dominated by hilly terrain and dense tropical forests, resulting in severely limited access to land transportation. Consequently, the local community relies heavily on river transportation to meet their mobility needs, goods distribution, and various socio-economic activities. This study aims to comprehensively examine the patterns of river transport usage, assess the availability and condition of supporting infrastructure and facilities, and identify the challenges and needs of users in the region. A quantitative approach was employed through the distribution of questionnaires and structured interviews, with results analyzed using descriptive statistics. The findings indicate that transport modes such as speedboats, longboats, inland vessels, and small outboard motorboats (ketinting) remain the primary means of transportation for residents. However, several issues persist, including inadequate dock infrastructure, low safety standards, and high operational costs. Therefore, this study recommends the development of sustainable infrastructure, improved service quality and safety measures, and stronger policy support from the government. These efforts are expected to promote equitable regional development and enhance the quality of life for the people of Mahakam Ulu, who depend on river transport as their main mode of connectivity. Abstrak Kabupaten Mahakam Ulu merupakan wilayah dengan kondisi topografi yang didominasi oleh perbukitan dan hutan tropis, sehingga akses transportasi darat menjadi sangat terbatas. Hal ini menyebabkan masyarakat setempat menggantungkan kebutuhan mobilitas, pengangkutan barang, serta kegiatan sosial dan ekonomi mereka pada moda transportasi sungai. Penelitian ini bertujuan untuk menelaah secara menyeluruh pola pemanfaatan transportasi sungai, menilai ketersediaan dan kondisi sarana serta prasarana pendukung, serta mengidentifikasi hambatan dan kebutuhan para pengguna transportasi di kawasan tersebut. Penelitian dilakukan menggunakan pendekatan kuantitatif melalui distribusi kuesioner dan wawancara terstruktur, dengan hasil yang dianalisis secara deskriptif. Temuan menunjukkan bahwa jenis moda speedboat, longboat, kapal pedalaman, dan perahu ketinting masih menjadi pilihan utama masyarakat. Namun, terdapat sejumlah tantangan seperti keterbatasan fasilitas dermaga, rendahnya standar keselamatan pelayaran, dan tingginya biaya operasional. Oleh karena itu, studi ini menyarankan perlunya pengembangan infrastruktur yang berkelanjutan, peningkatan mutu layanan dan keselamatan, serta dukungan kebijakan dari pemerintah. Rekomendasi ini diharapkan dapat mendukung pemerataan pembangunan wilayah serta meningkatkan kesejahteraan masyarakat Mahakam Ulu yang bergantung pada sungai sebagai jalur utama kehidupan mereka.